Obstáculos para implantação do assentamento funcional digital em uma instituição federal de ensino - Oliveira, Kaio Fernandes de (2024)
With the growing use of digital media in public sector administrative activities, such as the creation, processing and storage of documents, paper is gradually being replaced due to the practicality and space savings offered by digital formats. In this context, the Digital Functional Settlement (AFD) was developed within the bodies and entities of the Civil Personnel System of the Federal Public Administration (SIPEC), with the aim of storing and managing public servants' documents, simplifying access to information. However, not all public institutions have managed to make progress in implementing the AFD in their personnel management units. Given this scenario, the following question was raised: What are the obstacles to implementing the AFD in the personnel management units of a federal educational institution? The general aim of this research was therefore to analyze the obstacles to implementing AFD in the IFES.The methodology employed combined documentary and bibliographical research, with a qualitative approach that included a structured interview with the Director of People Management at the institution under investigation and the application of a questionnaire in its people management units. The results revealed that the implementation of the AFD is still at an early stage, facing a number of obstacles ranging from a lack of human resources to the infrastructure needed for the process, including hiring an outsourced company, acquiring equipment and the absence of archive professionals in the processes, as well as issues related to the internal regulation of procedures. Despite the measures adopted by the institution over time to boost implementation, there are still aspects to be considered in the face of the obstacles identified, making it necessary to adopt actions to promote this progress. Given this scenario, an action plan was drawn up to help the people management units overcome the obstacles and make progress in implementing the AFD